2021
DOI: 10.1155/2021/8917993
|View full text |Cite
|
Sign up to set email alerts
|

The Study of Yin-Chen-Hao-Tang Preventing and Treating Alcoholic Fatty Liver Disease through PPAR Signaling Pathway Based on Network Pharmacology and RNA-Seq Transcriptomics

Abstract: Background. Alcoholic fatty liver disease (AFLD) is the first stage of the alcoholic liver disease course. Yin-Chen-Hao-Tang (YCHT) has a good clinical effect on the treatment of AFLD, but its molecular mechanism has not been elucidated. In this study, we tried to explore the molecular mechanism of YCHT in improving hepatocyte steatosis in AFLD mice through network pharmacology and RNA sequencing (RNA-Seq) transcriptomics. Methods. Network pharmacological methods were used to analyze the potential therapeutic … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 22 publications
(20 reference statements)
0
6
0
Order By: Relevance
“…The obtained common targets of PK-hypoxia were imported from the STRING ( https://www.string-db.org/ ) database [ 31 ], and the restricted species was set as "Homo sapiens". The free targets were hidden by defaulting "Medium confidence" > 0.4 [ 32 ], the combined score was calculated, and the data was saved.…”
Section: Methodsmentioning
confidence: 99%
“…The obtained common targets of PK-hypoxia were imported from the STRING ( https://www.string-db.org/ ) database [ 31 ], and the restricted species was set as "Homo sapiens". The free targets were hidden by defaulting "Medium confidence" > 0.4 [ 32 ], the combined score was calculated, and the data was saved.…”
Section: Methodsmentioning
confidence: 99%
“…At the 11th day, all mice were sacrificed. The liver tissues were collected for the RNA-Seq transcriptome sequencing [ 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…Both geniposide and chlorogenic acid are found in traditional Chinese herbs, such as Zhizi (Gardenia fruit) and Yinchen (Herba Artemisiae Scopariae), respectively. The Yinchenhao Decoction contains both and is widely prescribed in Asian countries (like China and Japan) to prevent and treat alcoholic liver disease, acute pancreatitis, and cholestasis ( Xiang et al, 2016 ; Yan et al, 2017 ; Zhu et al, 2021 ). Our previous study has revealed that the combination of geniposide and chlorogenic acid (GC) improves and reduces high-fat diet (HFD)-induced NASH, improves intestinal barrier function ( Peng et al, 2018 ), and downregulates the expression of stearoyl-CoA desaturase (Δ-9-desaturase) (SCD1) in NAFLD mice ( Chen et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%